Delineation of MidXq28‐duplication syndrome distal to MECP2 and proximal to RAB39B genes. Issue 3 (17th June 2019) - Sinibaldi, Lorenzo; Parisi, Valentina; Lanciotti, Silvia; Fontana, Paolo; Kuechler, Alma; Baujat, Genevieve; Torres, Barbara; Koetting, Judith; Splendiani, Alessandra; Postorivo, Diana; Beygo, Jasmin; Garaci, Francesco G.; et al.
Abstract: Two distinct genomic disorders have been linked to Xq28‐gains, namely Xq28‐duplications including MECP2 and Int22h1/Int22h2‐mediated duplications involving RAB39B . Here, we describe six unrelated patients, five males and one female, with Xq28‐gains distal to MECP2 and proximal to the Int22h1/Int22h2 low copy repeats. Comparison with patients carrying overlapping duplications in the literature defined the MidXq28‐duplication syndrome featuring intellectual disability, language impairment, structural brain malformations, microcephaly, seizures and minor craniofacial features. The duplications overlapped for 108 kb including FLNA, RPL10 and GDI1 genes, highly expressed in brain and candidates for the neurologic phenotype. Abstract : A, B, Patient 1 brain‐magnetic resonance imaging (MRI) at age 40 years. (A) Mid‐line sagittal T2‐weighted picture: diffusely thin corpus callosum (black arrows); small brainstem and cerebellar vermis, widened extra‐axial cerebrospinal fluid spaces (stars). (B) Axial T2‐weighted image: IVventricle enlargement (stars). (C, D) Patient 4 brain‐MRI at age 7 years. (C) Mid‐line sagittal T2‐weighted image: corpus callosum hypoplasia, mainly of the posterior body (arrowheads) and isthmus (black arrow), enlarged cerebrospinal fluid cisterns (stars) and cerebellar vermis hypoplasia. (D) Axial T2‐weighted image: IV‐ventricle enlargement; moderate brainstem hypoplasia.